2019
DOI: 10.1186/s13018-019-1491-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altered proximal femoral geometry on predicting femoral stem anteversion in patients with developmental dysplasia of the hip

Abstract: BackgroundThe deformity of the proximal femur and acetabular in patients with developmental dysplasia of the hip (DDH) renders an intraoperative decision for ideal component placement challenging. We hypothesized that the altered morphology of calcar femorale (CF) in DDH patients changed the fixation mechanism of the cementless metaphyseal-filling stem and aimed to predict stem anteversion using proximal femoral anatomical parameters from preoperative CT.MethodsPreoperative and postoperative CT scans of 34 DDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We found the AM-CT at 10 mm height was better than that at 5 mm for predicting the PSA for DDH patients. These results may be because morphological characteristics of the distal femoral medullary cavity in DDH femurs tend to be more circular or elliptical ( 6 , 22 ), which created more difficulties in confirming the anterior and posterior cortex. Therefore, 5 mm height proximal to the base of the lesser trochanter of the CT slices may cause a slight deviation in confirming the midcortical-line compared to the 10 mm height group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found the AM-CT at 10 mm height was better than that at 5 mm for predicting the PSA for DDH patients. These results may be because morphological characteristics of the distal femoral medullary cavity in DDH femurs tend to be more circular or elliptical ( 6 , 22 ), which created more difficulties in confirming the anterior and posterior cortex. Therefore, 5 mm height proximal to the base of the lesser trochanter of the CT slices may cause a slight deviation in confirming the midcortical-line compared to the 10 mm height group.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate postoperative stem anteversion (PSA) in total hip arthroplasty (THA) is critical to achieving implant stability, the optimal range of motion (ROM), and avoiding impingement (1)(2)(3)(4)(5)(6)(7)(8). The combined anteversion technique, which considers the sum of acetabular cup anteversion and femoral anteversion, has been clinically proven to prevent implant impingement if controlled in a safe zone of 25°-50° (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Huang et al found that the version of calcar femorale or canal version at the inferior femoral neck, and canal version at CLT level all exhibited a strong positive correlation with stem version in patients with DDH. 30 However, CLT is a bony structure deviating from the main femoral canal, which cannot reflect the true axis of femoral canal. Besides, Tetsunaga et al demonstrated that the morphology of calcar femorale differed according to the severity of hip deformity, which made it less reliable to predict the stem version.…”
Section: Explorations For Better Preoperative Radiographic Methods To...mentioning
confidence: 99%
“…This difference may carry through to hip geometry in older adults. Moreover, complying with hip geometry when performing hip fracture surgery is essential for the outcome [ 16 ], and knowledge of hip geometry in older adults is necessary.…”
Section: Introductionmentioning
confidence: 99%